MENYINGKAP KARAKTER PRESIDEN SOEHARTO DARI BALIK TULISAN TANGAN - Lutfi Rahayu, Nur Qoyum Min; Afifah, Fadya Maulani; Prastiwi, Nanda Dwi Putri (BASINDO : jurnal kajian bahasa, sastra Indonesia, dan pembelajarannya, 2022)
This article analyzes Suharto's character through his handwriting using graphological theory. The purpose of this study was to determine Suharto's character through size, spacing, margins, shape, zone, and slant. The method used is a holistic approach and literature review data collection techniques. Source of data from handwritten drawing documents. The research results obtained show that Suharto was full of ambition and compassion, discipline and aggressive, wanted to be recognized and influential, thoughtful, and friendly.